Factores asociados al uso regular de fuentes de información en estudiantes de medicina de cuatro cuidades del Perú - Mejía, Christian R. (2015)
Objetives. To determine the factors associated with regular use of sources of information by medical students in four cities in Peru. Materials and methods. In this cross-sectional study, medical students were surveyed in four cities of Peru, gathering information on the use of 14 sources of information and other educational and computer variables. Frequent use of the information source was defined if the respondent reported that they access an information source at least once a week. P values were obtained by generalized linear models adjusted for each respondent site. Results. 2,300 students were surveyed. The median age was 21 years and 53% were women. Having received training in the use of sources increased the use in twelve of the consulted bases, not in SciELO (p=0.053) or in the university library (p=0.509).When adjusting for owning a laptop/netbook, these associations remained. After also adjusting for owning a smartphone the association was lost with the BVS Peru database (p=0.067). The association was also lost after making the final adjustment, if the respondent had carried out any research activities. Conclusions. The frequent use of sources of information is associated with having received training, conducting research and use of information technologies and communication. This should be taken into account in training programs and continuous improvement in undergraduate education.